Risk and protective factors for ASF in domestic pigs and wild boar in the EU, and mitigation measures for managing the disease in wild boar - European Food Safety Authority (EFSA); Anette Ella Boklund; Karl Ståhl; Miguel Ángel Miranda Chueca; Tomasz Podgórski; Timothée Vergne; José Cortiñas Abrahantes; Eleonora Cattaneo; Sofie Dhollander; Alexandra Papanikolaou; Stefania Tampach; Lina Mur (EFSA Journal)
Abstract Five epidemiological aspects of ASF were evaluated using literature reviews, field studies, questionnaires and mathematical models. First, a literature review and a case–control study in commercial pig farms emphasised the importance of biosecurity and farming practices, including the spread of manure around farms and the use of bedding material as risk factors, while the use of insect nets was a protective factor. Second, although wild boar density is a relevant known factor, the statistical and mechanistic models did not show a clear and consistent effect of wild boar density on ASF epidemiology in the selected scenarios. Other factors, such as vegetation, altitude, climate and barriers affecting population connectivity, also played a role on ASF epidemiology in wild boar. Third, knowledge on Ornithodoros erraticus competence, presence and surveillance was updated concluding that this species did not play any role in the current ASF epidemic in affected areas of the EU. Available scientific evidence suggests that stable flies and horse flies are exposed to ASFV in affected areas of the EU and have the capacity to introduce ASFV into farms and transmit it to pigs. However, there is uncertainty about whether this occurs, and if so, to what extent. Fourth, research and field experience from affected countries in the EU demonstrates that the use of fences, potentially used with existing road infrastructure, coupled with other control methods such as culling and carcass removal, can effectively reduce wild boar movements contributing to ASF management in wild boar. Fences can contribute to control ASF in both scenarios, focal introductions and wave‐like spread. Fifth, the use of gonadotropin‐releasing hormone (GnRH) vaccines as an immune contraceptive has the potential, as a complementary tool, to reduce and control wild boar populations. However, the development of an oral GnRH vaccine for wild boar still requires substantial additional work.